Necessity of the Needs Map in the Service Design for Smart Cities - An, Seyun; Kim, Sungwhan; Kim, Soyeon (Frontiers in Psychology, 2020)
Recently, it has become a hot issue how to involve actual service users in the service designs for smart cities since this is an important factor to determine the serviceability and sustainability of developed services. Reckless participations of users can make the service design process inefficient and cause a cost increase. So in this study we propose the necessity of Needs Map which can be applied to various stages of the service development and help service designers to make efficient and reasonable decisions without time consuming. This study defines Needs Map as a schematization of theoretical concepts for the Smart city planning in accordance with the framework of the service–technology-infrastructure-management (STIM). For gathering these theoretical concepts on Needs Map, we investigated many previous researches and held expert group meetings. Through Needs Map, various urban problems, statistical data, users’ needs in a smart city are classified and analyzed concept by concept, and these focused analysis results suggest a proper direction to researchers in the service development plan. To demonstrate experimentally the feasibility of Needs Map, we applied Needs Map in practice to a service design for the Smart city experience zone located in Daejeon, South Korea.